Population Genetic Structure of the Wedge Clam (Donax scortum) along the Andaman Sea Coast of Thailand - Supmee, Verakiat; Songrak, Apirak; Suppapan, Juthamas; Sangthong, Pradit (Journal of Fisheries and Environment, 2021)
The wedge clam (Donax scortum) is an important commercial species in Thailand. In our study, we performed an analysis of the genetic structure of the wedge clam population in the Andaman Sea along the coast of Thailand to provide information for developing a management plan. Partial sequences of the mitochondrial DNA cytochrome oxidase subunit I gene (mtDNA COI) with a size of 426 base pairs were investigated in 115 individuals, collected from four sampling sites within fishing grounds along the Andaman Sea coast of Thailand. Thirty-two haplotypes were observed. Haplotype diversity and nucleotide diversity were 0.887 and 0.00541, respectively. The population genetic analysis shows a lack of genetic structure, possibly caused by a high level of gene flow due to the high dispersal ability of wedge clam larvae. Demographic history tests reveal that the wedge clam population experienced expansion approximately 1,000 years ago. The results of our study can be used to guide the management of the wedge clam in this part of the Andaman Sea to maintain genetic diversity.